Infective Endocarditis In A Patient With Ventricular Septal Defect And Patent Ductus Arteriosus - Sattwika PD., et al (ACI (Acta Cardiologia Indonesiana), 2017)
Infective Endocarditis In A Patient With Ventricular Septal Defect And Patent DuctusArteriosus